Contralateral Prophylactic Mastectomy among Women with Pathogenic Variants in BRCA1/2: Overall Survival, Racial, and Ethnic Differences - Sukh Makhnoon; Angelica M. Gutierrez Barrera; Roland Bassett; Aimaz Afrough; Isabelle Bedrosian; Banu K. Arun (The Breast Journal)
Background. Patients with unilateral breast cancer carrying pathogenic variants in BRCA1/2 have the option to undergo contralateral prophylactic mastectomy (CPM). However, differences in CPM use and survival outcomes following CPM are poorly understood in this high-risk population, in part due to a lack of data from contemporary clinical cohorts. The objective of this study was to evaluate post-CPM overall survival (OS) and related racial/ethnic differences in a contemporary clinical cohort. Methods. We retrospectively reviewed the medical records of women with a personal history of unilateral breast cancer carrying pathogenic variants in BRCA1/2 who were diagnosed between 1996 and 2012. Genetic test results, self-reported demographic characteristics, and clinical factors were abstracted from electronic medical records. Results. Of 144 BRCA-positive patients, the majority were White (79.2%, n = 114). Overall, 56.1% (n = 81) of all BRCA1/2 carriers chose to undergo CPM, with no racial/ethnic difference in CPM election (p = 0.78). Of 81 patients who underwent CPM, there is strong evidence of a difference in survival between the racial/ethnic groups, with White patients having the highest OS compared to non-White patients (p = 0.001). Of the 63 patients who did not undergo CPM, there is no racial/ethnic difference in overall survival (p = 0.61). In multivariable cox regression, adjusted for demographic and clinical characteristics, OS was significantly lower among non-Whites than in Whites (HR = 0.39, p = 0.04). Conclusions. Evaluation of a contemporary clinical cohort of BRCA-positive women with unilateral breast cancer showed no racial/ethnic difference in CPM use, but there was a significant difference in post-CPM overall survival.